READING THE TERM DALÂL IN THE QUR’AN - Ahmad Baliyo Eko Prasetyo (Millah: Journal of Religious Studies, 2008)
Book Review:Book Title : Kesesatan dalam Perspektif Al-Qur’anAuthor : Aibdi RahmatPublisher : Pustaka Pelajar, YogyakartaEdition : I, March 2007Content : viii + 228 pages